Training Interpreters of Languages of Lesser Diffusion in an English Medium, Non Language Specific Interpreting Classroom - Crezee, Ineke (Estudios de Traducción, 2026)
This article will outline the training of interpreters working with languages of lesser diffusion in the non-language specific interpreting classroom with English as the medium of instruction at one New Zealand University. The paper will reflect on the findings of previous studies, before turning to the approaches used at the university in question, and reflecting on any remaining challenges. This paper will introduce Languages with Less Existing Specialist Terminology (LLESTs) as a new term to reflect the difficulty interpreters and translators working with certain languages have in identifying existing equivalent terms for specialist terminology. The author will argue that while Languages of Lesser Diffusion (LLDs) are not necessarily Languages with Less Existing Specialist Terminology (LLESTs), LLESTs are almost always LLDs and that this requires special attention in the interpreter training setting. The article will discuss initiative by the New Zealand government to allow practising interpreters to complete a NAATI Endorsed Qualification so as to ensure a more even quality of interpreting in the public service setting. She will provide details on the number of students working with LLDs in the 2024 academic year, while discussing some of the challenges of non-language specific interpreter training at her university, together with some of the approaches, including the use of GoReact for interpreting practice, self-reflection and language-peer feedback.